Triceratops - Fritz, Sandy and George Olshevsky (Mankato, MN Smart Apple Media, 2003)
Presents information on Triceratops, including physical characteristics, diet, habitat, known social organization, close relatives, and areas where fossils have been found.
Keywords: Triceratops; Dinosaurs